2013 ACM / IEEE International Symposium on Empirical Software Engineering and Measurement 2013
DOI: 10.1109/esem.2013.25
|View full text |Cite
|
Sign up to set email alerts
|

Using Ensembles for Web Effort Estimation

Abstract: Accurate effort estimation enables effective managerial decisions to be made by project managers when embarking on a project, and this trend also applies when managing Web projects. Web development has steadily increased over the years; research into identifying sound ways to improve the effort estimates being made by thousands of Web companies worldwide would be valuable. Looking at the state of the art in the domain of Web resource estimation, we show that numerous effort estimation techniques have been inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 37 publications
(143 reference statements)
4
27
0
Order By: Relevance
“…Finally, many of the techniques that were applied to software effort estimation have also been used for Web effort estimation [4,27], which also include the use of ensembles [5]. Mendes pioneered this field, and also led the creation of the Tukutuku database, which is to date the only crosscompany database on Web project data [31].…”
Section: Software Effort Estimationmentioning
confidence: 99%
“…Finally, many of the techniques that were applied to software effort estimation have also been used for Web effort estimation [4,27], which also include the use of ensembles [5]. Mendes pioneered this field, and also led the creation of the Tukutuku database, which is to date the only crosscompany database on Web project data [31].…”
Section: Software Effort Estimationmentioning
confidence: 99%
“…The assessment stage conducted by Scott-Knott algorithm that function only works on balanced design and designed to help researchers cooperate with analysis of variance (ANOVA) experiments. In this study, the design chosen is a repeatable measurement equal to a complete random block design (RCDB) [2]. Scott-Knott is algorithm hierarchy classification used as an exploration data analysis tool that its application with analysis of variance (ANOVA).…”
Section: The Competency Assessment Through Scott-knott Algorithmmentioning
confidence: 99%
“…In which comparison of treatment ratio is an important step to find homogeneous and non-homogeneous groups, it means that each situation leads to a significant F test [10]. Adaptation of random complete block design (RCDB) explained in the following general equation: (2) in which g is the gap value of each individual, μ is the actual of entire average treatment (mean rate). While, is the effect of treatment to or the difference of competence level 2, is the effect from block to j or individuals within this framework, and is error in the form of effect comes from the experimental unit to j which is subject to treatment to , is the employee (treatment) and j is the level 2 competency.…”
Section: The Competency Assessment Through Scott-knott Algorithmmentioning
confidence: 99%
“…Replication of previous methods and Snott-Knott algorithm [45] were used to shortlist best out of available techniques for ensembles. The results obtained in this research work showed better estimation accuracy by adapting ensembles in comparison to solo estimation models and identified 15 best estimation ensembles [46]. Giulio B., et al, 2015, in their research work proposed a methodology, Web Framework Points(WFP) to estimate efforts for web application development using CMF.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Damir Azhar, et al 2013, conducted a study to investigate the accuracy of ensembles for web effort estimation at early stages of web development. Replication of previous methods and Snott-Knott algorithm [45] were used to shortlist best out of available techniques for ensembles.…”
Section: Literature Reviewmentioning
confidence: 99%